The Implementation of the Merdeka Curriculum in Enhancing Student Creativity at SDN 002 Ibul, Pucuk Rantau District, Kuantan Singingi Regency, Riau Province - Syoviana, Elvi; Andre, Lesis; Afriwes, Afriwes; Yanti, Rena Putri (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
The Merdeka Curriculum began to be implemented at SDN 002 Ibul in 2022 as part of the government's effort to improve the quality of education in accordance with the National Education Standards (SNP). However, to date, it remains uncertain whether the implementation of the Merdeka Curriculum at SDN 002 Ibul has truly succeeded in enhancing student creativity in the learning process. This issue remains unanswered both theoretically and practically in the field. Therefore, this study aims to examine and analyze the extent to which the Merdeka Curriculum contributes to enhancing student creativity at SDN 002 Ibul.This research uses a qualitative approach with a descriptive method. The main instrument in this study is the researcher herself, who acts as the primary tool for collecting descriptive and contextual data. The sources of data consist of both primary and secondary data. Data collection techniques include observation, interviews, and documentation. Data analysis is conducted through the stages of data reduction, data presentation, and drawing conclusions. Data validity is tested through credibility (internal validity), transferability (external validity), dependability (reliability), and confirmability (objectivity) techniques.The research findings indicate that the implementation of the Merdeka Curriculum at SDN 002 Ibul can significantly enhance student creativity. This is evident from the achievement of 12 creativity indicators: having a high curiosity, frequently asking meaningful questions, offering many ideas and suggestions to solve problems, being able to express opinions spontaneously without fear, possessing and appreciating a sense of beauty, having independent views and expressing them without being easily influenced by others, having a strong sense of humor, possessing vivid imagination, offering unique solutions and ideas (originality), being able to work independently, enjoying trying new things, and being able to develop or elaborate on an idea. Overall, it can be concluded that the Merdeka Curriculum can enhance student creativity at SDN 002 Ibul through learning freedom and the role of the teacher as a facilitator.